Energy transfer in aqueously dispersed organic semiconductor nanoparticles - Roozbeh, Ashkan; Bassi, Maiara de Jesus; Pereira, Adriano Bezerra; Roman, Lucimara Stolz; Buckup, Tiago; Heisler, Ismael A. (The journal of physical chemistry. C, Energy, materials, and catalysis, 2020)
Organic photovoltaics (OPVs) hold promise for a cost-effective, eco-friendly, and sustainable technology to harvest solar energy. However, the widespread application of OPVs has been hindered mostly due to their intrinsic narrow absorption band and environmental impacts caused by toxic solvents required during the synthesis. In this work, we investigated energy transfer dynamics in water-dispersed polymeric nanoparticles (NPs) of F8T2, MDMO-PPV, and their mixtures (bicomponent) synthesized by the miniemulsion technique. Using femtosecond transient absorption and time-resolved fluorescence spectroscopy, we showed that Förster resonance energy transfer (FRET) can be promoted in the bicomponent NPs on an ultrafast time scale and modulated upon the variation in polymer concentrations. The higher FRET efficiency achieved for the bicomponent NPs compared to reports for single-component donor-acceptor systems implies that this design strategy may be utilized in primary building blocks of ternary architecture. Our results suggest that the water-dispersed polymeric bicomponent NP of F8T2/MDMO-PPV is a promising candidate to be incorporated in ternary structures of OPVs in combination with acceptors, such as fullerene C60, to extend the absorption band, increase the energy transfer efficiency, and facilitate exciton dissociation.
Gesehen am 01.02.2021